2009
DOI: 10.1007/s00405-009-0952-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Aggressive papillary’ thyroid microcarcinoma

Abstract: The objective of this study is to highlight the fact that papillary thyroid microcarcinoma can be aggressive, requiring therapeutic management similar to that of other differentiated thyroid cancers. This 8-year retrospective study concerned 187 surgical patients managed in an ENT and Head and Neck surgery department for thyroid cancer. 65 patients were found to have papillary microcarcinoma. 41 microcarcinomas were considered to be aggressive because of the presence of several risk factors such as larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 19 publications
0
34
0
6
Order By: Relevance
“…6 In papillary thyroid microcarcinoma, nodal metastases have been reported in the range of 6-66.4% cases. 4,5,7,19,[22][23][24] In the present study, node dissection was performed in 70% (n ¼ 87) of the patients. Of these, 28% of patients had metastatic lymph nodes, and 88% of patients with nodal metastasis had microcarcinomas positive for the mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In papillary thyroid microcarcinoma, nodal metastases have been reported in the range of 6-66.4% cases. 4,5,7,19,[22][23][24] In the present study, node dissection was performed in 70% (n ¼ 87) of the patients. Of these, 28% of patients had metastatic lymph nodes, and 88% of patients with nodal metastasis had microcarcinomas positive for the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Clinicopathological factors, eg, age more than 45 years, tumor size greater than 5 mm, male sex, multifocality, lymph nodes metastasis, and extrathyroidal extension have been reported to predict poor prognosis. 4,7,8 In recent years, a T1799A point mutation in the v-raf murine sarcoma viral oncogene homolog B1 (BRAF) resulting in a valine-to-glutamic acid switch at codon 600 (V600E) has emerged as a marker of aggressive behavior in papillary thyroid carcinoma. 9 A few studies have suggested that this mutation may predict aggressive behavior in papillary microcarcinoma too.…”
mentioning
confidence: 99%
“…Two main difficulties arise from these modern guidelines: (i) a subset of these tumours progresses and metastasises (Roti et al 2006, Page et al 2009(ii) patients, when presented with a cancer diagnosis, often prefer comprehensive therapy, which leaves them with the best prognosis and the lowest risk of recurrence, often despite the potential cost of any associated treatment morbidity. Although current tumour staging systems are unable to guide therapy in papillary microcarcinomas, the potential for use of TSH to assist in assessing prognosis is appealing.…”
Section: Serum Tsh In Different Thyroid Cancer Subtypesmentioning
confidence: 99%
“…Most of the variations of the thyroid gland are due o a partial persistence of the median thyroglossal duct [4].We also observed a female fetus with agenesis of isthmus ith isolated lobes. Failure of the development of the ntire gland, or part of the gland, results in agenesis or emi agenesis, which may be unilateral or isthmic [6][7][8][9][10][11][12][13][14]Many workers claim that the absence of isthmus is uite rare in humans [7,8]. The frequency of the presence of pyramidal lobes could be a source of pitfalls in hyroidectomy during preoperative diagnosis on images [9].Braun et al [9] reported a pyramidal lobe was found to be present in 55% of the cadavers and it was found more frequently in men than in omen.…”
Section: Discussionmentioning
confidence: 99%